Oxygen yields as a constraint on feedback processes in galaxies - Lara López, Maritza A. (2019)
We study the interplay between several properties determined from optical and a combination of optical/radio measurements, such as the effective oxygen yield (yeff), the star formation efficiency, gas metallicity, depletion time, gas fraction, and baryonic mass (Mbar), among others. We use spectroscopic data from the SDSS survey, and H I information from the ALFALFA survey to build a statistically significant sample of more than 5000 galaxies. Furthermore, we complement our analysis with data from the GASS and COLD GASS surveys, and with a sample of star-forming galaxies from the Virgo cluster. Additionally, we have compared our results with predictions from the EAGLE simulations, finding a very good agreement when using the high-resolution run. We explore in detail the Mbar–yeff relation, finding a bimodal trend that can be separated when the stellar age of galaxies is considered. On one hand, yeff increases with Mbar for young galaxies [log(tr) < 9.2 yr], while yeff shows an anticorrelation with Mbar for older galaxies [log(tr) > 9.4 yr]. While a correlation between Mbar and yeff has been observed and studied before, mainly for samples of dwarfs and irregular galaxies, their anticorrelated counterpart for massive galaxies has not been previously reported. The EAGLE simulations indicate that AGN feedback must have played an important role in their history by quenching their star formation rate, whereas low-mass galaxies would have been affected by a combination of outflows and infall of gas.